Technology for Invasive Species Removal in Ballast Water - Worachananant, Pasinee; Saengsomrit, Waranphat; Poungcharean, Santi (Burapha Science Journal, 2026)
Contamination of alien species in ballast water is one of the four major threats to marine ecosystems. There are more than 7,000 species of organisms found in ballast water. Without proper treatment, these organisms were released into new environments and causing a devastating effect on native species and the ecological changes. Therefore, the removal efficiency of technology including temperature, Ultraviolet, ozone and microbubble to treat 2 phytoplankton (Chaetoceros sp. and Chlorella sp.) and 2 zooplanktons (Crab larvae in Zoea stag and Artemia sp.) were investigated. The results showed that microbubble treatment is the most effective technology which can treat up to 100% of all 4 types of plankton within 20 minutes. Ultraviolet treatment is the second most effective technology, which can treat up to 100% of all 4 types of plankton within 240 minutes. Followed by ozone treatment which can treat zooplankton (100% within 360 min) better than phytoplankton (56.87% within 360 min). The least efficient method was temperature treatment, which can treat zooplankton (100% within 300 min) better than phytoplankton (38.08% within 1,440 min).